Modeling 2D swash zone hydro/morphodynamics using discontinuous Galerkin finite element method - Aboulatta, Waddaa (2020)
This PhD study aims to develop a new robust and efficient 2D numerical coupled hydro/morphodynamics model for general swash zone simulation. Non-linear shallow water equations (NSWEs) are used for describing the swash zone hydrodynamics, while a modified advection diffusion equation (ADE) is used for suspended sediment transport simulation, and an Exner type equation is used for bed change simulation. The Discontinuous Galerkin finite element method (DG-FEM) is used for solving this system of governing equations. However, to be able to simulate general swash zone processes, absorbing generating boundary condition is implemented, as well as a new efficient wet/dry treatment is developed. Even though, solving the fully coupled NSWEs and bed change equation using DG-FEM is very difficult, solving the weakly coupled system was not in a strait forward manner. Three different methods using two different approaches are tested, nonetheless, none of them offered satisfactory results for fast bed changing simulations. This motivated the development of a new approach (bed reconstruction method).